2021
DOI: 10.1108/el-09-2020-0265
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis on digital libraries and academic search engines from the dual-route perspective

Abstract: Purpose Digital libraries and academic search engines have developed as two important online scholarly information sources with different features. The purpose of this study is to compare digital libraries and academic search engines from the perspective of the dual-route model. Design/methodology/approach Research hypotheses were developed. Potential participants were recruited to answer an online survey distributing at Chinese social media out of which 251 responses were deemed to be valid and used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Esmaeili et al (2021) conducted a study on the roadmap of Iranian digital academic libraries in the context of cloud infrastructure and the development of cloud libraries. Cao et al (2021) investigated the role of digital libraries and academic search engines to support the educational mission of the institutions. The study revealed that modern age users frequently utilized digital information resources to make completion of the assigned educational and research-based tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Esmaeili et al (2021) conducted a study on the roadmap of Iranian digital academic libraries in the context of cloud infrastructure and the development of cloud libraries. Cao et al (2021) investigated the role of digital libraries and academic search engines to support the educational mission of the institutions. The study revealed that modern age users frequently utilized digital information resources to make completion of the assigned educational and research-based tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Haji Zeinolabedini (2017), Salaba et al (2018), Possemato (2018), Tallerås et al (2018), Aalberg (2019), Beene et al (2020), Cao et al (2021), Chen (2023). To identify and analyse the challenges associated with FRBR implementation.…”
Section: Research Objectivesmentioning
confidence: 99%
“…They provide students with visual and textual materials to analyse and evaluate, fostering discussions about authority, authorship, bias, audience, and inclusion/exclusion. On top of that, easier cataloguing and circulation for librarians are stated by Cao et al (2021) within the paper. FRBR promotes a user-centric approach to information retrieval by focusing on the user's tasks and goals.…”
Section: Advancement Of Cataloguing Effortsmentioning
confidence: 99%
“…The rapid increase in the size of web information has introduced new challenges for search engines in the manner in which they retrieve search results. In reality, there are still many situations in which users are presented with inaccurate or very poor search results [3].…”
Section: Introductionmentioning
confidence: 99%